Echocardiographic evaluation of myocardial structural and functional changes in patients with stage 5 chronic kidney disease before and after kidney transplantation - M. Sh. Khubutiya; E. V. Shuvalova; O. N. Rzhevskaya; L. T. Khamidova; A. A. Ivannikov; Kh. G. Alidzhanova; A. G. Balkarov; I. V. Dmitriev (Трансплантология (Москва), 2024)
Introduction. Chronic kidney disease, stage 5, leads to structural remodeling of the myocardium, and heart failure. Kidney transplantation promotes normalization of structural and functional parameters of the myocardium through reverse remodeling with an improvement of its systolic function.Aim. To evaluate structural and functional changes of the myocardium in patients before and after kidney transplantation, using echocardiography.Material and methods. A retrospective cross-sectional study included 111 individuals of whom 36 patients underwent evaluation for kidney transplant waiting list placement program (Group I), and 51 patients received kidney transplants from deceased donors (Group II). Group III consisted of 24 individuals without kidney pathology. All patients underwent transthoracic two-dimensional echocardiography using the Phillips Epiq 7 device to determine the structural and functional parameters of the heart, including the use of speckle-tracking technique to assess longitudinal and circumferential myocardial deformation of the left ventricle.Results. There were no statistically significant differences in transthoracic echocardiography results between patients in Group I and Group II. When compared to the parameters of patients in Group III, statistically significant differences were found in the following parameters: volume and volume index of the left atrium, end-diastolic volume index, left ventricular mass index, interventricular septum thickness and posterior wall thickness of the left ventricle, as well as diastolic function parameters (E/A). Patients in Group I and Group II had significantly higher values of left atrium diameter: 32 (26.0;38.0) mmHg and 31.0 (27.3;40.0) mmHg, respectively, (p1-2=0.949), while in Group III this parameter value was 22.5 (20.8;25.3) mmHg (p1-3<0.001, p2-3<0.001). Correlation analysis revealed statistically significant correlations between left ventricular mass index and global circumferential strain (r=0.41, p=0.0027), as well as between E/e' ratio and left ventricular mass index (r=0.323, p=0.00197). It was found that after 3 months post kidney transplantation, there was a decrease in the left atrium diameter, volume, and volume index. The values of left atrium diameter immediately after kidney transplantation and after 3 months were 40 (32.5;45) mmHg and 35 (25.5;41.0) mmHg (p=0.049); those of the left atrium volume were 62.5 (50.0;77.3) and 51.5 (47.5;64.5) ml (p=0.03); and those of the left atrium volume index were 33.4 (29.3;40.2) and 28.3 (25.5;33.6) ml/m2 (p=0.01) respectively.Conclusions. Patients with chronic kidney disease stage 5 have a high incidence of functional and structural abnormalities of the left heart chambers; left ventricular mass index positively correlates with E/e' and global circumferential strain. At 3 months after kidney transplantation, there was a slight positive trend manifested in the form of a decrease in left atrium diameter and a decrease in left ventricle volume. Further dynamic study of this group of patients in the long term after kidney transplantation is planned.